Usability testing of the Pathway app: engaging stakeholders to improve access to mental health support for students - Oti, Olugbenga; Foley, Sarah; Pitt, Ian (Frontiers in Digital Health, 2025)
BackgroundMental health difficulties are highly prevalent among university students. Evidence shows that a majority of university students do not seek professional mental health support for their difficulties. Help-seeking technologies provide an opportunity to facilitate students' access to suitable services. This study aims to evaluate the usability of the Pathway prototype, which helps students find support that fits their needs and preferences.MethodsWe conducted three cycles of usability testing with 26 participants comprising students, experts and stakeholders. Students were asked to “think aloud” as they completed tasks using the Pathway prototype. In addition, they were asked to complete the Single Ease Question and rate their experience of using the prototype. Experts and stakeholders were asked to provide feedback following a presentation of the app. The data were analysed using a table of changes approach, thematic analysis and descriptive quantitative analysis.ResultsFollowing each usability testing cycle, several changes were made to the Pathway prototype. Participants reported that Pathway was a useful app to help students find appropriate support.ConclusionIn comparing Pathway to current methods of searching for support, students believed that Pathway was quicker, more trustworthy and provided more privacy in searching for support.